Nano Online 2016
DOI: 10.1515/nano.11671_2015.158
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of NiO two-dimensional grainy films and their high-performance gas sensors for ammonia detection

Abstract: Semiconductor NiO two-dimensional grainy films on glass substrates are shown to be an ammonia-sensing devices with excellent comprehensive performance, such as the good stability, short response time, outstanding recovery performance, excellent sensitivity, and selectivity. The morphology and structure analysis of gas sensing materials indicated that the as-fabricated NiO films was uniform and highly ordered porous structure on substrates, which composed of small size particles with diameters ranging from 8 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…As indicated in the spectra, for all samples characteristics peaks at 407, 437, 475, 500, 520, 560, 607, 668, and 820 cm −1 correspond to Ni-O stretching vibration bonds as reported in literature [29,34,35] but with use of others deposition methods. Table 2 summarizes obtained results in this study in agreement with other results carried out in literature 52]. To give confirmation to the observed 820 cm −1 absorption strength vibration, in the case of 0.05 and 0.1 M sprayed sample (Figures 4(d) and 4(e)), calculated wave number (in cm −1 as units) using Hook's law in simple harmonic oscillator model was done.…”
Section: Fourier Transform Infrared (Ft-ir) Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…As indicated in the spectra, for all samples characteristics peaks at 407, 437, 475, 500, 520, 560, 607, 668, and 820 cm −1 correspond to Ni-O stretching vibration bonds as reported in literature [29,34,35] but with use of others deposition methods. Table 2 summarizes obtained results in this study in agreement with other results carried out in literature 52]. To give confirmation to the observed 820 cm −1 absorption strength vibration, in the case of 0.05 and 0.1 M sprayed sample (Figures 4(d) and 4(e)), calculated wave number (in cm −1 as units) using Hook's law in simple harmonic oscillator model was done.…”
Section: Fourier Transform Infrared (Ft-ir) Analysissupporting
confidence: 88%
“…With increasing of precursor concentration from 0.03 to 0.05 M, the commencement of crystallization was observed. It is seen from XRD patterns that only single peak appears at 2 = 37.24 ∘ , which is attributed to the (111) diffraction peak and clearly indicated that the NiO phase exists under its face centered cubic (fcc) structure, which is in good agreement with Joint Committee on Powder Diffraction Standards (JCPDS card number 47-1049) [52]. From XRD patterns, with respect to limit detection, no other impurity peaks were detected.…”
Section: Structural Propertiessupporting
confidence: 73%
“…A similar observation was reported by Wang et al for a 300-nm-thick 2D NiO film on Ta glass substrate. 21…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation was reported by Wang et al for a 300-nm-thick 2D NiO film on Ta glass substrate. 21 The Mn 2þ ion has only a marginally smaller ionic radius of 0.67 A ˚than the Ni 2þ ion (0.69 A ˚) in the same octahedral coordination. Therefore, Mn 2þ is expected to occupy the Ni 2þ site in the NiO matrix without significantly changing the crystal structure.…”
Section: Morphological Observationsmentioning
confidence: 97%
“…In this work, NiO thin films were fabricated on BK7 and silicon by thermal oxidation of sputtered nickel films. It is well known that the size, structure and morphology of the films are the essential parameters for those applications [17][18][19][20][21][22]. The physical properties of the metal oxide thin films could be modified by adding suitable doping materials like Li, Cu, Au and Ag [1,14,23].…”
Section: Introductionmentioning
confidence: 99%